THE ROLE OF PRODUCTIVE SKILLS IN FOREIGN LANGUAGE LEARNING - Atadjanova, D.A.; Jaksimuratova, K.O. (SCIENCE and SOCIETY, 2023)
This article shows the importance of productive skills as speaking and writing in students’ learning and main advantages are provided.